An Educational Intervention to Improve the Sleep Behavior and Well-Being of High School Students - Colt, Alexandra (PRiMER, 2019)
OBJECTIVE: The objective of this study was to determine whether a sleep education intervention improves knowledge of sleep, sleep behaviors, and depression in high school freshmen. METHODS: We recruited student volunteers at a single magnet high school in Los Angeles, California through their health class. Twenty-four freshmen participated and 18 students (17 female, 1 male) completed pre- and postsurveys. Curriculum consisted of 4 hours of after-school interactive lectures emphasizing sleep physiology, benefits of sleep, what impacts sleep, and methods to improve sleep, followed by a 9-week sleep behavior change journal. Pre- and postsurveys measuring both sleep behaviors and knowledge, and a Patient Health Questionnaire-9 depression screening were administered to participants prior to and after the intervention. We used t tests and χ(2) tests to analyze knowledge and behavior change. RESULTS: Subjects improved in average sleep hours per night (preintervention 6.9 hours to postintervention 7.8 hours, P=.0134), and average weekend night bedtime (11:36 pm to 10:54 pm, P=.0307). CONCLUSIONS: This school sleep behavior intervention demonstrated students’ average sleep hours per night and weekend bedtime improved after the lecture and sleep journal intervention. This suggests a sleep education intervention may benefit this population. Further studies are needed to demonstrate effectiveness of this education over time, across sexes, and in high-risk students.